Peluang Gen-Z Dalam Meraih Kesuksesan Melalui Investasi Saham - Nindya Eka Sobita; M Iqbal Harori; Rendy Satya Aji Paluvi; Iqrima Aini (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This service activity aims to add insight into investment and stock trading, as well as things that need to be considered to become investors and before investing. This dedication is one of the ways to anticipate the bad effects of the rise of investments under the guise of stocks but fake investments. This is due to the lack of investment knowledge for the z generation so that it is easy to be lured in by investments with high yields. In addition, the purpose of this service is to provide an introduction and socialization about investing in the Indonesian Capital Market for all new students within the Faculty of Social and Political Sciences, University of Lampung. This service also provides a clear description that with the Introduction and Training of Investments in the Indonesian Capital Market, it is hoped that this service can be input for participants to add insight into investment and stock trading, as well as matters that investors need to consider before investing. It is also hoped that this can be input for the management of the FISIP UNILA Investment Gallery in providing the best service to the public regarding investment and capital market knowledge so as to increase public interest in investing in the Indonesian capital market.